2019
DOI: 10.1038/s41401-018-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide phosphoribosyltransferase aggravates inflammation and promotes atherosclerosis in ApoE knockout mice

Abstract: Nicotinamide phosphoribosyltransferase (Nampt) is the rate-limiting enzyme of nicotinamide adenine dinucleotide (NAD) salvage biosynthesis in mammals, and is involved in fundamental physiological processes and pathophysiology of many diseases. Thus far, however, the role of Nampt in atherosclerosis development is still in debate. In this study, we crossed global Nampt transgenic mice (Nampt-Tg) with a well-established atherosclerosis animal model (ApoE knockout mice, ApoE −/−) to generate ApoE −/− ;Nampt-Tg mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…It should be noted that cardiac-specific overexpression of Nampt also stimulated production of cytokines, including TNF-␣ and MCP-1, and activation of NF-B signaling at baseline and during PO. We and others have shown that Nampt itself can act as an inflammatory cytokine when overexpressed (14). Although myocardial infiltration of inflammatory cells was not significantly elevated in Tg-Nampt mice compared with in WT mice at baseline or in response to PO, it is possible that upregulation of proinflammatory mechanisms may contribute to the exacerbation of PO-induced cardiac dysfunction in Tg-Nampt mice.…”
Section: Discussionmentioning
confidence: 72%
“…It should be noted that cardiac-specific overexpression of Nampt also stimulated production of cytokines, including TNF-␣ and MCP-1, and activation of NF-B signaling at baseline and during PO. We and others have shown that Nampt itself can act as an inflammatory cytokine when overexpressed (14). Although myocardial infiltration of inflammatory cells was not significantly elevated in Tg-Nampt mice compared with in WT mice at baseline or in response to PO, it is possible that upregulation of proinflammatory mechanisms may contribute to the exacerbation of PO-induced cardiac dysfunction in Tg-Nampt mice.…”
Section: Discussionmentioning
confidence: 72%
“…The levels of NAMPT decrease with aging due to chronic inflammation, oxidative stress, and DNA damage [ 20 ]. In the cardiovascular system, NAMPT exacerbates atherosclerotic inflammation and promotes atherosclerosis development in ApoE mice [ 13 ]. NAMPT promotes pulmonary vascular remodeling, and its inhibition potentially represents a therapeutic strategy for pulmonary arterial hypertension (PAH) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT has been reported to be involved in various diseases and conditions, such as obesity, nonalcoholic fatty liver disease (NAFLD), type 2 diabetes mellitus (T2DM), cancer, and aging [ 11 ]. In the cardiovascular system, NAMPT promotes atherosclerosis development by exacerbating atherosclerotic inflammation [ 13 ]. NAMPT inhibits myocardial injury by regulating NAD and ATP levels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nampt is involved in many important biological processes, including survival, apoptosis, metabolism and angiogenesis (16). As a cytokine, an elevated concentration of Nampt has been observed in several inflammatory and autoimmune disorders, such as sepsis, atherosclerosis, systemic lupus erythematosus and Crohn's disease (17)(18)(19)(20). Previous studies have demonstrated an elevated plasma Nampt concentration in Hashimoto's thyroiditis (HT) patients (14).…”
Section: Discussionmentioning
confidence: 99%